Bridging communication gaps assessing residents' awareness and acceptability of the proposed and existing physical developments in Sta. Barbara - Caderao, Ma. Thesa; Dalino, Liariz; Duazo, Shaira Mae; Eclarinal, Precious Mariel; Juanga, Krisha Faye
Government would cease to exist without people to govern. In the Philippines setting, the Local Government Code of 1991 grants power to Local government is tasked to play the role of delivering basic services to the public. Recent studies related to Local Government Management have begun to verify the relationship between performance of local government and its citizen's feedback. In this study, the researchers attempts an assessment of residents' awareness and acceptability on the proposed and existing physical developments in the town of Sta. Barbara. To support the evaluation, the researchers used shaping factors like effectiveness of current communication means in transmitting information regarding the various developments happening in the town, sufficiency, accuracy, clarity, and accessibility of data given by the local government unit of Santa Barbara as well the responsiveness of government personnel to inquiries. While some studies have been certain that public participation is one of the medium of communication that the government use to facilitate involvement in local governing, there are uncovered cases referring to whether the application is feasible in less-developed countries like the Philippines where there is also a lacking of ethical considerations in the political dimension. The primary data for this study were collected through obtained copies of the Development Concepts from the Municipal Planning Head of Sta. Barbara and then supplemented by conducting surveys to six barangays. Key results have showed that in general, the residents are satisfied on the performance of the government however some concerns were revealed. The quality of information is excellent but the means of circulation is somewhat problematic. The results of acquiring information through non-government means seemed to be more apparent than obtaining information from government means. In relation to this, the group commends bridging the gap between the Municipal leaders and residents through : allowing Punong Barangays to have access on Community Development straight from Municipal Office, investing in enhancing the established government-owned radio-broadcasting system as well as exercising the practice of annual feedback method.